An Attempt for Developing the Measurement System of Reaction Force from Snow Surface for Private Ski Boots by Compact Force Sensors. (2015) - Saito, Ayuko; Doki, Hitoshi; Kondo, Akiko; Hirose, Kiyoshi
Abstract: This paper proposes a new measurement system which measures the reaction force from snow surface for skiing. It is important to analyze the reaction force from snow surface of the skier gliding on the actual snow field to clarify the mechanism of ski turns. In the previous studies, we have used the measurement system of reaction force from snow surface installing the 6-axis force sensor. The system installed the 6-axis force sensor to each foot, and the skier had to carry a data recording PC. Therefore, the entire system was heavy. Furthermore, the system could be used only for the specific ski boots. In this study, we developed a new measurement system of reaction force from snow surface for skiing installing the compact 3-axis force sensors. The 6-axis force components could be calculated by using the information of the compact 3-axis force sensors. We developed a special data logger for saving the sensor outputs, and the skier could glide without loading PC. The system is smaller and lighter than the previous system. The system can be attached between private ski boots and bindings. The system can be adjusted the size of private ski boots. The body of the system was produced by using the personal 3D printer. The verification experiment was conducted to confirm the accuracy of the system. The results of the 6-axis force components calculated by the system were compared to the values of the 6-axis force sensor. These results approximately correspond in all axes. We conducted the measurement experiment of the skier gliding on the actual snow field, and we showed the reaction force from snow surface of the skier by using the system. The system can be applied to motion analysis of the skier gliding on the actual snow field.